Sintomatologia pós-traumática e funcionamento executivo - Bertagnolli, Ana Cristina Coitino (2013)
Individuals who are exposed to traumatic events and develop Posttraumatic Stress Disorder (PTSD) might present psychological, behavioral and cognitive difficulties after being exposed to trauma. Symptoms of PTSD include reexperience of the traumatic event, avoidance of stimuli related to the trauma and increased excitability. Regarding cognitive impairments, in addition to impairment in episodic memory and attention, PTSD has also been associated with impairments in executive functions. The impairments are not associated only with the formal diagnosis of PTSD and were also identified in individuals with high symptomatology of the disorder. This study aims to investigate cognitive performances on measures of executive functions in individuals with PTSD symptoms. For this, two studies were conducted, one theoretical and one empirical, presented in form of articles. The theoretical article sought to establish an overview of executive impairments shown by individuals exposed to trauma with either formal diagnoses of PTSD, history of PTSD or PTSD symptoms through a systematic review. The empirical article aimed to assess the cognitive performance of 29 subjects exposed to trauma and high scores on SPTSS inhibition, working memory and cognitive flexibility symptoms. These individuals had their performances compared to 24 individuals who were never exposed to any traumatic event, matched in age and education. Considering the high prevalence of disorders presented in comorbidity with PTSD the control group was formed by individuals who were being treated for any psychological or psyquiatric disorder other than PTSD. The control group consisted of clinical population because the presence of other psychopathologies can cause impairments on executive function. PTSD symptoms were assessed with the Screen for Posttraumatic Stress Symptoms (SPTSS), that aims to identify reexperience, avoidance and increased excitability symptoms in individuals exposed to trauma. A descriptive study with cross-sectional design was conducted. The group with individuals exposed to trauma and high PTSD symptoms showed poorer performance on Trail Making Test (p=0,009), an instrument used to assess cognitive flexibility. These impairments can lead to difficulties in adopting new cognitive strategies needed to deal with cognitive and environmental triggers that lead to the memory of the traumatic event. Only impairments in cognitive flexibility were identified, suggesting that some but not all EF components are affected by PTSD